2017
DOI: 10.7554/elife.23043
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the molecular mechanisms of myasthenia gravis and their therapeutic implications

Abstract: The nicotinic acetylcholine receptor (nAChR) is a major target of autoantibodies in myasthenia gravis (MG), an autoimmune disease that causes neuromuscular transmission dysfunction. Despite decades of research, the molecular mechanisms underlying MG have not been fully elucidated. Here, we present the crystal structure of the nAChR α1 subunit bound by the Fab fragment of mAb35, a reference monoclonal antibody that causes experimental MG and competes with ~65% of antibodies from MG patients. Our structures reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…Muscle-type nicotine AChR, neurotransmitter member of the ligand-gated ion channels family, is a pentameric molecule located in the in the middle of the post-synaptic membrane, with 5 subunits (α1 2 βδ and ε) in the adult muscle [36,37]: the acetylcholine binds the receptor at the interface of the α-δ and the α-ε subunits. In the α1 subunit, between the amino acids 67-70 is located the main immunogenic region that plays an important role on the pathogenesis of MG [38].…”
Section: Myasthenia Gravis and Acetylcholine Receptormentioning
confidence: 99%
“…Muscle-type nicotine AChR, neurotransmitter member of the ligand-gated ion channels family, is a pentameric molecule located in the in the middle of the post-synaptic membrane, with 5 subunits (α1 2 βδ and ε) in the adult muscle [36,37]: the acetylcholine binds the receptor at the interface of the α-δ and the α-ε subunits. In the α1 subunit, between the amino acids 67-70 is located the main immunogenic region that plays an important role on the pathogenesis of MG [38].…”
Section: Myasthenia Gravis and Acetylcholine Receptormentioning
confidence: 99%
“…A single IgG monoclonal antibody molecule can crosslink two nAChR molecules (Tzartos and Starzinski‐Powitz ). Recent X‐ray structural studies have confirmed that a single mAb35 molecule is able to bind two α1 subunits from two adjacent monomers – thereby crosslinking them – whereas it does not bind to the two α1 subunits within a single nAChR monomer (Noridomi et al ). Moreover, antibodies directed against the MIR of the receptor have been reported to form oligomeric complexes larger than the dimer (Conti‐Tronconi et al ; Tzartos et al ).…”
mentioning
confidence: 99%
“…Given their established myasthenogenic role, extensive efforts have been put into characterizing the interactions between MG autoantibodies and nAChR using biochemical [45,46,[48][49][50][51][52][53], structural [22,[54][55][56], and modeling approaches [57]. More recently, the first crystal structures of human (pdb code: 5HBT) and mouse (pdb code: 5HBV) nAChR ECD bound by the Fab fragment of an EAMG autoantibody, Fab35 were determined [58]. Both crystal structures are very similar, so the discussion here will focus mainly on the human complex (pdb code: 5HBT).…”
Section: Structural Studies Of the Complexes Between Nachr Ecd And Eamentioning
confidence: 99%
“…As mentioned above, nAChR α1 is just one subunit of the nAChR pentamer and is intrinsically unstable, making the expression of wild type nAChR α1 ECD in stable soluble form very challenging. However, as discussed earlier in this chapter, crystallography studies of nAChR α1 ECD in recent years have accumulated extensive experience and knowledge in designing strategic mutations to improve the stability and expression level of nAChR α1 ECD protein while preserve the binding of MIR-directed MG autoantibodies [22,31,58] These progresses will greatly facilitate the approach to using engineered antigen chimera to specially inhibit and eliminate nAChR-specific B cells for MG treatment.…”
Section: Nachr-specific B Cell Inhibition and Depletion With Engineermentioning
confidence: 99%